2020
DOI: 10.18666/jorel-2020-v12-i2-9802
|View full text |Cite
|
Sign up to set email alerts
|

Improving Ecological Behavior in Outdoor Recreation Through Mindfulness Interventions: A Mixed Methods Inquiry

Abstract: Outdoor recreation professionals have long sought to impact environmental behavior of participants. Mindfulness and nature connection have recently been explored as possible constructs to impact environmental behavior. The purpose of this study was to better understand the impact of mindful outdoor recreation trips on college students' nature connectedness and ecological behavior. We used explanatory mixed methods approach to explore the relationship between mindfulness, nature connection, and ecological behav… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
9
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 11 publications
(9 citation statements)
references
References 33 publications
0
9
0
Order By: Relevance
“…Quite the contrary, Frank et al reported several counter cases, where mindfulness practice reinforced self-confirmative reasons to not consume sustainably. Finally, one mixed-methods study found that combining mindfulness with outdoor tourism made participants more ready to preserve nature (Deringer et al, 2020).…”
mentioning
confidence: 99%
“…Quite the contrary, Frank et al reported several counter cases, where mindfulness practice reinforced self-confirmative reasons to not consume sustainably. Finally, one mixed-methods study found that combining mindfulness with outdoor tourism made participants more ready to preserve nature (Deringer et al, 2020).…”
mentioning
confidence: 99%
“…Collectively, these results also suggest that mindfulness training may be a useful tool for supporting ST and NC in the service of encouraging pro-environmental behavior. Current evidence suggest that mindfulness training can increase decentering and ST in novice meditators (Dambrun, 2016; Dambrun et al, 2019; Garland & Fredrickson, 2019; Hanley, Dambrun & Garland, 2020; Hanley et al, 2018; Hanley & Garland, 2019) and can encourage NC (Aspy & Proeve, 2017; Deringer et al, 2020), while both dispositional mindfulness (Barbaro & Pickett, 2016; Hanley, Bettmann, et al, 2020) and being mindfully outdoors (Deringer et al, 2020) are associated with pro-environmental behavior. Experimental studies are now needed to explore how decentering, ST, and NC unfold over different time scales (i.e., a single mindfulness meditation practice or a multiweek mindfulness-based intervention), and whether these changes translate into pro-environmental behavior.…”
Section: Discussionmentioning
confidence: 99%
“…Outdoor education is a crucial tool for promoting not only pro-environmental attitudes and behaviors, but also connection to nature (Pirchio et al, 2021). Various outdoor education professionals understand their platform in the world of environmental activism and have sought methods to increase ecologically responsible behavior in participants (Deringer et al, 2020). However, many of the practices in outdoor education focus on nature contact and ecological-scientific education as the key pathways towards sustainability and conservation goals rather than nature connection (Pirchio et al, 2021).…”
Section: The Role Of Outdoor Education In Promoting Nature Connectionmentioning
confidence: 99%
“…However, the impact of habits and our daily behaviors is seldom accounted for in studies on pro-environmental behavior (Linder et al, 2021). Most studies highlight instead virtues (Martin et al, 2009), values, attitudes (Linder et al, 2021), or ecological knowledge to catalyze pro-environmental behavior (Deringer et al, 2020). These topics fail to extensively reach their intended outcomes because they start in the middle of the ripple, not with the stone that creates the ripple.…”
Section: Fostering Habits Of Reciprocity and Connection Through Outdo...mentioning
confidence: 99%